PENGARUH BAURAN PEMASARAN (MARKETING MIX) DAN PERILAKU KONSUMEN TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN JUS BUAH SEGAR BANDAR LAMPUNG - Mufri Wedanimbi Octaviani; Yaktiworo Indriani; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This research aims to analyze: the respondent characteristiccs of fresh fruit juice consumers in Bandar Lampung; the effect of marketing mix including product, price, place, and promotion of consumer’s decision making on buying fresh fruit juice in Bandar Lampung; the social, personal and psychological factors of the consumer on the purchase of fresh fruit juice in Bandar Lampung; and the dominant factors in the marketing mix and consumer behavior on the decision to purchase fresh fruit juice in Bandar Lampung.  This research was conducted at Zainal Pagar Alam Street, Purnawirawan Street, and Pramuka Street in Bandar Lampung.  The research samples of 105 college students were chosen on purpose when they bought fresh fruit juice during January 2013 until February 2013. SEM analysis used to answer the research aims and the Correlation of Rank Spearman test was used to determine the relationship between variables. The results of the research showed that most of the consumers were female collage students and most of them was 21 years old. The latent variables of marketing mix that significantly affected on the fruit juice purchase were product and price variables.  The personal and social factors significantly effected the purchase decision of fruit juice in Bandar Lampung. The product variable was the most dominant variable affected on consumer decision making of fresh fruit juice purchase. Key words: consumer behavior, fresh fruit juice, marketing mix, SEM